The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/healthcare11131973
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cross-Sectional Study of Acute Coronary Syndrome Patients’ Quality of Life and Drug Prescription Patterns at Riyadh Region Hospitals, Saudi Arabia

Abstract: Acute coronary syndrome (ACS) is a leading cause of cardiovascular-related morbidity and mortality worldwide. The present study investigated the health-related quality of life (HRQOL) and drug prescribing patterns in ACS patients at Riyadh hospitals in Saudi Arabia. This study was a 12-month prospective cross-sectional study that included 356 patients with ACS. The current study showed that younger male (67.42%) and urban (75.84%) patients suffered more from ACS. Moreover, most patients with NSTEMI (51.69%) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“… 11 A 12-month prospective cross-sectional study of 356 patients with acute coronary syndrome demonstrated that the most prescribed drug was statins (93%), followed by antiplatelet drugs and anticoagulants in Saudi Arabia. 12 In a database from Australia’s Pharmaceutical Benefits Scheme, the prevalence of long-term statins users over the age of 65 had increased 35.6% with ten years. 13 Meanwhile, atorvastatin is the most commonly used statin in each year and the new use of high-intensity statins had also increased from 23.6% to 30.5% in a 10-year trend analysis.…”
Section: Epidemiology Of Statins Usementioning
confidence: 99%
“… 11 A 12-month prospective cross-sectional study of 356 patients with acute coronary syndrome demonstrated that the most prescribed drug was statins (93%), followed by antiplatelet drugs and anticoagulants in Saudi Arabia. 12 In a database from Australia’s Pharmaceutical Benefits Scheme, the prevalence of long-term statins users over the age of 65 had increased 35.6% with ten years. 13 Meanwhile, atorvastatin is the most commonly used statin in each year and the new use of high-intensity statins had also increased from 23.6% to 30.5% in a 10-year trend analysis.…”
Section: Epidemiology Of Statins Usementioning
confidence: 99%
“…Notably, obesity is associated with an earlier onset of CAD [5] . No matter the patient's age, risk factors like obesity, hypertension, and smoking might affect how ACS manifests clinically obesity, hypertension, and smoking all have an impact on how clinically apparent ACS is in individuals of all ages [6] . Gender disparities have been noted in the symptoms reported by patients admitted for ACS.…”
Section: Introductionmentioning
confidence: 99%
“…New research from Saudi Arabia revealed that patients with ACS were more likely to be male (67.4%) and urban (75.8%). In addition, 33.4% of NSTEMI patients had grade 1 dyspnea (51.7%); however, patients with STEMI had a higher risk for mortality [ 14 ]. In terms of the management of acute cardiac ischemia, once intervention therapy is started during the first seventy minutes, the mortality decrease approaches half [ 15 ].…”
Section: Introductionmentioning
confidence: 99%